Pengaruh Persepsi Kemudahan, Persepsi Kegunaan, dan Persepsi Risiko terhadap Keputusan Pembelian menggunakan Shopee Paylater pada Gen Z: Indonesia - Rokhman, Nur; Fadilla, Syakira (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2026)
This study aims to analyze the influence of perceived ease, perceived usefulness, and perceived risk on the decision to use Shopee PayLater among Gen Z. Data collection was conducted using a purposive sampling approach, which is part of non-probability sampling, involving 120 participants. The analysis process relies on primary data from questionnaires evaluated with the help of SPSS software. The results of this study indicate that: (1) Perceived ease (X1) has a significant positive effect on the decision to purchase using Shopee Paylater among Gen Z, (2) Perceived usefulness (X2) has a significant positive effect on the decision to purchase using Shopee Paylater among Gen Z, (3) Perceived risk (X3) has a significant negative effect on the decision to purchase using Shopee Paylater among Gen Z.